2023
DOI: 10.3390/microorganisms11112662
|View full text |Cite
|
Sign up to set email alerts
|

Pectobacterium carotovorum Subsp. brasiliense Causing Soft Rot in Eggplant in Xinjiang, China

Wei He,
Wenfang Luo,
Junhui Zhou
et al.

Abstract: An outbreak of stem rot in eggplants was observed in Heshuo County, Xinjiang, during winter 2021–2022 in about 12–35% of the eggplants in the region (about 40 hm2). The infected tissues yielded a total of four bacterial strains, which were subsequently subjected to physiological and biochemical assays as well as molecular identification. Based on these analyses, the pathogen was identified as Pectobacterium carotovorum subsp. brasiliense. The pathogenicity was confirmed through the fulfillment of Koch’s postul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Moreover, this representative member of the interleukin family is involved in inflammation, immune regulation, and cancer development ( Lopetuso et al, 2013 ). IL-1β stimulates inflammatory cells to enter the intestine via autocrine and paracrine mechanisms, thereby causing tissue damage and inflammation ( He et al, 2023 ). Remarkably decreased IL-1β levels in a study indicated that probiotics reduce inflammatory factor levels ( Wang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this representative member of the interleukin family is involved in inflammation, immune regulation, and cancer development ( Lopetuso et al, 2013 ). IL-1β stimulates inflammatory cells to enter the intestine via autocrine and paracrine mechanisms, thereby causing tissue damage and inflammation ( He et al, 2023 ). Remarkably decreased IL-1β levels in a study indicated that probiotics reduce inflammatory factor levels ( Wang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The healthy chili fruits were surface-sterilized via immersion in 10% (v/v) sodium hypochlorite for 10 min, then in 75% (v/v) ethanol for 10 min, and finally dried under sterile conditions. Each bacterial isolate was prepared in 0.1% peptone at a dilution of 1 × 10 8 UFC/mL [29] and vortexed for 1 min, then 10 µL of each bacterial suspension was inoculated in triplicate on the chili fruits' surfaces, which were punctured with a sterile needle and inoculated at that point. Negative controls were inoculated with 0.1% peptone.…”
Section: Isolation Of Pathogen Organismmentioning
confidence: 99%